Mineralogic and physico-chemical studies of Lahad Datu bentonite - Abd. Karim, Khairuddin; Junin, Radzuan (1992)
The commencement of production of activated clay by the local industry has created the demand for bentonite (montmorillonite) clay which is the basic raw material used in the manufacturing process. In the search for this material, field augering and sampling programme were undertaken in areas which collectively form the Segama Group near lahad Datu, Sabah.